Activity performance and kinetics for glycerol carbonylation with urea over Zn-Co mixed metal oxide catalyst - Kondawar, Sharda E.; Kasar, Gaytri B.; Khatua, Angshuman S.; Rode, V, Chandrashekhar (Canadian Journal of Chemical Engineering, 2023)
Efficient carbonylation of glycerol using urea with Zn-Co mixed metal oxide (MMO) catalyst has been achieved. Various methods of catalyst preparation were explored for glycerol carbonate (GC) synthesis. The optimized method of catalyst preparation was found to be co-precipitation (CP) with a Zn:Co ratio of 70:30, achieving 81% glycerol conversion with 97% GC selectivity. X-ray diffraction (XRD) studies revealed the formation of ZnO, Co-3 O-4, and spinel ZnCo2O4 phases. Thermal treatment given to the catalyst allows insertion of Zn cations into Co3O4 lattice forming ZnCo2O4 phase which was also evidenced in X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy. Herein, for the first time, reaction kinetics was studied to propose the rate equation, based on which a plausible reaction pathway is proposed involving two-site adsorption of glycerol (basic site) and urea (acidic site), which undergo carbonylation followed by cyclization into GC. A recycle study and hot filtration test have proven the reusability of the catalyst.
Keywords: Carbonylation; cyclic carbonate; Glycerol; kinetics; mixed metal oxide